Immunometabolism and Pulmonary Infections: Implications for Protective Immune Responses and Host-Directed Therapies - Rao, Martin; Dodoo, Ernest; Zumla, Alimuddin; Maeurer, Markus (Frontiers in Microbiology, 2019)
The biology and clinical efficacy of immune cells, based on examination of samples from patients with infectious diseases or cancer, are associated with metabolic programming. Genetic and epigenetic signatures, imprinted on the host immune and stromal cells by the invading pathogen, shape disease pathophysiology as well as clinical disease outcomes. Directly linked to the immuno-metabolic axis is the role of the host microbiome, which is also discussed here in the context of productive immune responses to lung infections. We also present host-directed therapies (HDT) as a clinically viable strategy to refocus dysregulated immunometabolism in patients with infectious diseases, which requires validation in early phase clinical trials as adjuncts to conventional antimicrobial therapy. These efforts are expected to be continuously supported by newly generated basic and translational research data to gain a better understanding of disease pathology while devising new molecularly defined platforms and therapeutic options to improve the treatment of patients with pulmonary infections, particularly in relation to multidrug-resistant pathogens.